Power electronic control in electrical systems - Acha, Enrique (Oxford : Newnes, 2002)
Within this book the fundamental concepts associated with the topic of power electronic control are covered alongside the latest equipment and devices, new application areas and associated computer-assisted methods. *A practical guide to the control of reactive power systems *Ideal for postgraduate and professional courses *Covers the latest equipment and computer-aided analysis.
Preface; Electrical power systems -- an overview; Power systems engineering -- fundamental concepts; Transmission system compensation; Power flows in compensation and control studies; Power semiconductor devices and converter hardware issues; Power electronic equipment; Harmonic studies of power compensating plant; Transient studies of FACTS and Custom Power equipment; Examples, problems and exercises; Appendix; Bibliography; Index.
0
Includes bibliographical references and index.
Keywords: Electric power systems -- Control; Power electronics; Electric power systems -- Control; Power electronics; Electronic books